Assessing Impulsivity in Humans and Rodents: Taking the Translational Road - Esteves, Madalena; Moreira, Pedro Silva; Sousa, Nuno; Leite-Almeida, Hugo (Frontiers in Behavioral Neuroscience, 2021)
Impulsivity is a multidimensional construct encompassing domains of behavioral inhibition as well as of decision-making. It is often adaptive and associated with fast responses, being in that sense physiological. However, abnormal manifestations of impulsive behavior can be observed in contexts of drug abuse, attention-deficit/hyperactivity disorder (ADHD), among others. A number of tools have therefore been devised to assess the different facets of impulsivity in both normal and pathological contexts. In this narrative review we systematize behavioral and self-reported measures of impulsivity and critically discuss their constructs and limitations, establishing a parallel between assessments in humans and rodents. The first rely on paradigms that are typically designed to assess a specific dimension of impulsivity; either within impulsive action – inability to suppress a prepotent action –, or impulsive choice – which implies a decision that weighs the costs and benefits of the options. On the other hand, self-reported measures are performed through questionnaires, allowing assessment of impulsivity dimensions that would be difficult to mimic in an experimental setting (e.g. positive/negative urgency; lack of premeditation, etc.), and which are therefore difficult (if not impossible) to measure in rodents.